Investors’ perception towards socially responsible investment - a study with special reference to stock market investors in Kerala - Laya K S (PG Department of Commerce & Research, Vimala College (Autonomous), 2023)
Socially Responsible Investment (SRI) incorporates environmental, social and corporate governance factors (ESG factors) into the investment decision-making process. It is an investor-driven philosophy of inclusion of best-in-class companies, or companies with good corporate social behaviour and CSR (Corporate Social Responsibility) practices andexclusion of unethical companies or sin stocks from the investment portfolio. It is a tool to attain the UN Sustainable Development Goals (SDGs). SRI is a firmly established investment segment in developed countries but has yet to gain momentum in developing countries like India. Lack of awareness of social responsibility-themed investment products and ESG risks and opportunities, lack of uniformity in ESG disclosures and reporting, lack of trustworthy ESG data, and lack of promotion from the regulatory authorities are the challenges that hinder the growth of SRI. Environmental threats created by corporates, challenges paused by pandemics, increased incidence of social issues and corporate scams induced the importance of considering social responsibility in stock market investment. These created SRI as a relevant topic under research in India over the past few years, including in South India. Even though the state of Kerala is well known for its outstanding achievement in education, health, e-governance and sustainable development, the concept of SRI is not prevalent in Kerala. Thus, in this context, the present study investigates how stock market investors in Kerala perceive and understand socially responsible investment (SRI) and what factors influence their perception and behaviour towards SRI. This study is descriptive in nature, and a purposive sampling method using a structured questionnaire was used to collect data from stock market investors in Kerala. The study found that awareness of SRI is limited across investors in Kerala. The awareness is slightly higher for female investors and investors with higher educational backgrounds. It is also found that investors in Kerala positively perceive SRI. Attitude, financial performance, and environmental factors positively influence investors' behavioural intention to invest in SRI. The comparative performance analysis of sustainability-themed portfolios confirmed that these funds yielded a reasonable return with lower risk and volatility from 1st April 2017 to 31st March 2022. Thus, SRI is an investment opportunity for investors to satisfy their financial and non-financial objectives. 62 % of Kerala's population is below 40 years old; previous studies have indicated that young investors are more inclined towards SRI. Therefore, if investors in Kerala acknowledge the SRI opportunities and benefits, it can attract more people to stock trading and contribute to the environment, society, and the economy.
Thesis (Ph.D)- Vimala College (Autonomous), PG Department of Commerce & Research, 2023.
Keywords: Socially responsible investment; ESG factors; Corporate social responsibility; Sustainable development goals; Best-in-class